Mapping Management of Innovation and Leadership in the Sustainability of an Organization; Bibliometric Analysis 2020-2022 - Zudi Rahmawan; Wulandari Destri; Parjiyati; Rika Wulansari; Rr. Tisie Yuhara; Ariff Muhamed (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2023)
Purpose - ArticleThis paper presents and discusses the impact of an innovation implemented by leadership on the sustainability of an organization which is taken from mapping through biblometric analysis. In order to compete with other organizations, organizations must have innovation and be innovative in looking for new ideas or breakthroughs. In fact, there have been many studies related to management innovation. But here we are interested in examining how much researchers who conduct innovation management research directly related to leadership use bibliometric analysis through VOSViewer. Design/methodology/approach - We use a bibliometric method and review related to Innovation and Leadership management. We obtained the data source for the bibliometrics through the Scopus database. Findings and Discussion – The results of research with mapping using the keyword "Management Innovation" show two clusters. In the first cluster there are 2 interrelated elements, namely study and innovation which are closely related to the innovation itself. In the second cluster there is only Development related to innovation. Innovation Connectivity between clusters can be seen through the nodes. The bigger the node, the higher the frequency of occurrence. Conclusion - The study can be concluded that Innovation Management and Leadership are very closely related. It has been proven that in the last 2 years there have also been many studies highlighting management innovation but most of them have researched management innovation in the education sector. In addition, Innovation Management also ranks first on the vosviuwers search page. The citations used for research also reach thousands in the article. Articles on innovation management also reach hundreds of articles published annually by various studies.